Contemporary Outcomes for Advanced‐Stage Classical Hodgkin Lymphoma in the U.S.: Analysis of Surveillance, Epidemiology, and End Results Database. (29th August 2019) - Guru Murthy, Guru Subramanian; Szabo, Aniko; Hamadani, Mehdi; Fenske, Timothy S.; Shah, Nirav N.
Abstract: Background: Advanced‐stage Hodgkin lymphoma (HL) is a curable malignancy, although outcomes remain poor in certain patients. It remains unclear if recent advances have improved their population‐level survival over time. Materials and Methods: Using the Surveillance, Epidemiology, and End Results database, we identified patients aged ≥18 years with stage III or IV classical HL as the first primary malignancy, diagnosed between 2000 and 2014 and treated with chemotherapy. Patients were stratified by date of diagnosis into three groups (2000–2004, 2005–2009, 2010–2014) to assess the trends in overall survival (OS). Results: A total of 9, 042 patients with a median age of 41 years were included. The use of frontline radiation therapy decreased in each period (21.3% [2000–2004] vs. 15.5% [2005–2009] vs. 10.7% [2010–2014]; p < .001). Three‐year OS was significantly higher for patients diagnosed between 2010 and 2014 (81.8%) and 2005 and 2009 (80.6%) compared with 2000 and 2004 (78.5%; p = .0008 and .02, respectively). Whereas outcomes were poorest in the age >60 cohort, similar improvements were also seen in 3‐year OS over the three time periods within this patient population. On multivariate analysis, diagnosis in the earlier period and minority race were associated with higher mortality. Females and married patients had significantly lower mortality risk. Conclusion: Survival of patients with advanced‐stage HL has continued to improve over time, suggesting the impact of evolving treatment approaches. Three‐year OS in the contemporary period remains inadequate at 81.8%, highlighting the need for continued research to improve their outcomes. Implications for Practice: This article evaluates contemporary outcomes for advanced‐stage Hodgkin lymphoma (HL) in the U.S. using the Surveillance, Epidemiology, and End Results database. Although overall survival (OS) has improved in each 5‐year period since 2000, the 3‐year OS from 2010 to 2014 remains inadequate at 81.8% and is limited by patient demographics. New therapies are indicated to improve clinical outcomes in advanced‐stage HL. Abstract : This article reports trends, discrepancies, and determinants of survival in a cohort of patients with advanced stage Hodgkin lymphoma, based on a retrospective analysis of the SEER database.